Silicon carbide joining layer material and method of making and use thereof
Patent Information
- Application Number
- CN202410291341.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-03-14
AI Technical Summary
当稀土硅碳陶瓷应用于连接材料时,具有低残余应力、抗辐照、抗酸碱等优异性能,但是由于其本身强度低于传统结构陶瓷,限制了其进一步应用
[0034]1.本发明创造性地采用稀土氢化物、碳化硅和碳化硅晶须为原料,首先通过固相合成和球磨工艺制备出稀土硅碳陶瓷细粉,并确保碳化硅晶须均匀分散于陶瓷粉体中。通过滚筒混料、烘干、预压和烧结等一系列严谨工艺步骤,首次成功制备出碳化硅连接层材料,其中碳化硅晶须分布均匀且结构完整,证实了前期分散工艺的有效性。
Smart Images

Figure CN118206377B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic materials technology, and relates to a silicon carbide bonding layer material, its preparation method and application. Background Technology
[0002] Silicon carbide possesses numerous superior properties, including low density, high strength, high modulus, and excellent thermal and chemical stability. Therefore, silicon carbide ceramics and their composites have wide applications in aerospace, automotive, and many other fields, and are even considered one of the next-generation nuclear structural ceramics. However, its strong covalent bonds result in high strength but poor toughness. When machining complex-shaped ceramic parts, stress concentration at sharp corners easily leads to breakage, making it impossible to process into large-sized, complex structural components like metals. This severely limits the development and application of advanced ceramic materials. In practical applications, to overcome the machining difficulties, joining techniques are often used to connect relatively simple ceramic components to fabricate complex and large-sized structural parts. This also allows for the repair of parts, improving the service life and reliability of the ceramics.
[0003] Rare earth silicon carbide compounds (chemical formula RE3Si2C2, where RE represents rare earth elements) are a novel type of layered ceramic material. Their structural characteristics are similar to the well-known MAX phase family, possessing a unique two-dimensional layered stacking structure. This structure endows them with special physical and chemical properties, including significant metallic conductivity and non-magnetic properties under normal conditions. Their magnetic order transition temperatures are all below 60K, ensuring a non-magnetic state at room temperature.
[0004] Given the unique structure and excellent electromagnetic properties of rare-earth silicon carbide compounds, as well as their ability to co-melt with silicon carbide at high temperatures to form a liquid phase, researchers both domestically and internationally have conducted in-depth research and multifaceted application attempts on these materials over the past few years. For example, they have been used as additives in the sintering process of ceramic materials (such as SiC and Si3N4) to reinforce silicon carbide ceramics (C... f / SiC、SiC f The bonding properties of rare earth silicon carbide (SMC) composites and their potential applications in the development of electromagnetic wave absorbing materials are being explored. When rare earth silicon carbide ceramics are used as bonding materials, they exhibit excellent properties such as low residual stress, radiation resistance, and acid and alkali resistance. However, their lower strength compared to traditional structural ceramics limits their further application.
[0005] Chinese patent application document (publication number: CN117069505A) discloses a silicon carbide fiber bonded ceramic and its preparation method. The preparation method uses silicon carbide fiber, rare earth materials and molten salt medium as raw materials. A rare earth carbide coating is prepared on the surface of silicon carbide fiber by molten salt method. Then, silicon carbide fiber bonded ceramic is prepared by hot pressing sintering. However, the product prepared by molten salt method is prone to contain a large number of oxide and chloride impurities. At the same time, pure rare earth metals are easy to oxidize due to the water washing process and the high activity of rare earths. Even if rare earth hydrides, which are more stable than pure rare earth metals, are used, a large number of oxides still exist. Summary of the Invention
[0006] The purpose of this invention is to address the aforementioned problems in the prior art by proposing a silicon carbide bonding layer material with higher thermal conductivity and flexural strength.
[0007] The objective of this invention can be achieved through the following technical solution: a method for preparing a silicon carbide bonding layer material, the method comprising:
[0008] S1. Rare earth hydrides and silicon carbide are mixed, and then ball-milled and calcined to obtain rare earth silicon carbide ceramic powder.
[0009] S2. Mix rare earth silicon carbide ceramic powder with silicon carbide whiskers, and then obtain composite ceramics through sintering.
[0010] In the above-mentioned method for preparing a silicon carbide bonding layer material, the average particle size of rare earth hydrides is 50-200 μm, the average particle size of silicon carbide is 0.1-1 μm, and the average diameter of silicon carbide whiskers is 0.2-1 μm.
[0011] In the above-mentioned method for preparing a silicon carbide bonding layer material, the molar ratio of rare earth hydride to silicon carbide in step S1 is (1-2):1. In this invention, the molar ratio of rare earth hydride to silicon carbide is (1-2):1. Too much or too little of these ratios will lead to the formation of impurity phases, affecting the overall performance of the silicon carbide bonding layer material.
[0012] In the above-mentioned method for preparing a silicon carbide bonding layer material, the rare earth element in the rare earth hydride is at least one of Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.
[0013] In the above-mentioned method for preparing a silicon carbide bonding layer material, the ball milling speed in step S1 is 100-300 r / min, and the ball milling time is 2-8 h.
[0014] In the above-mentioned method for preparing a silicon carbide bonding layer material, step S1 involves calcination with a temperature increase of 5-20℃ / min to 900-2000℃ and a holding time of 2-10h.
[0015] In the above-mentioned method for preparing a silicon carbide bonding layer material, the rare earth silicon carbide ceramic powder in step S1 is ball-milled, and the particle size after ball milling is 1-10 μm. In this invention, the rare earth silicon carbide ceramic powder needs to be ball-milled, and the particle size needs to be controlled to be 1-10 μm; otherwise, it will affect the uniformity and density of subsequent sintering, leading to a reduction in the overall performance of the silicon carbide bonding layer material.
[0016] As a preferred method, rare earth silicon carbide ceramic powder is obtained by adding anhydrous ethanol and zirconium oxide ball milling beads, followed by planetary ball milling, rotary evaporation and sieving, to obtain rare earth silicon carbide ceramic powder with a particle size of 1-10 μm.
[0017] In the above-mentioned method for preparing a silicon carbide bonding layer material, the amount of silicon carbide whiskers added in step S2 is 1-15% of the mass of rare earth silicon carbide ceramic powder. In this invention, if too little silicon carbide whiskers are added, they will not have a toughening effect; if too much are added, it will lead to difficulties in dispersing the silicon carbide whiskers, and at the same time, the high stress will lead to a decrease in mechanical properties.
[0018] Preferably, step S2 mixing specifically includes: adding anhydrous ethanol and zirconium oxide ball milling beads to the mixed powder of silicon carbide whiskers and rare earth silicon carbide ceramics, mixing with a horizontal drum, rotary evaporation and sieving, and then loading it into a graphite mold to pre-press it into a block.
[0019] Further optimization involves using a horizontal drum mixer with a rotation speed of 100-300 r / min and a mixing time of 8-16 h.
[0020] In the above-mentioned method for preparing a silicon carbide bonding layer material, step S2 sintering is carried out in a protective atmosphere, with a heating and cooling rate of 1-100℃ / min, a temperature of 900-2000℃, a holding time of 10-60min, and a pressure of 20-50MPa.
[0021] The core raw materials for the silicon carbide bonding layer material of this invention are rare earth hydrides, silicon carbide, and silicon carbide whiskers. Unlike traditional methods, this invention first employs a carefully designed solid-state synthesis process, reacting rare earth hydrides with silicon carbide powder to successfully prepare the basic powder of rare earth silicon carbide ceramics. To further improve the dispersibility and reactivity of the powder, this invention utilizes a meticulous ball milling technique to refine the initially synthesized rare earth silicon carbide ceramic powder to a small particle size suitable for subsequent composite processes, ensuring uniform particle size and ease of subsequent processing.
[0022] This invention innovatively employs a drum mixing technique to mix silicon carbide whiskers with rare-earth silicon-carbide ceramic powder. This ensures that the silicon carbide whiskers are fully and uniformly dispersed throughout the ceramic powder, overcoming the agglomeration problems that may occur with conventional mixing methods. This achieves excellent dispersion and embedding of silicon carbide whiskers at the microscale. Through rigorous post-mixing treatments, including drying, pre-pressing, and precisely controlled sintering, this invention successfully prepares a silicon carbide bonding layer material. Notably, the silicon carbide whiskers in the final silicon carbide bonding layer material sample obtained through this invention are not only uniformly distributed but also retain their original one-dimensional structural integrity. This strongly demonstrates the efficiency and uniqueness of the initial dispersion process in this invention.
[0023] In addition to innovations in process technology and microstructure, the preparation method provided by this invention significantly improves the overall performance of silicon carbide bonding layer materials. Compared to pure rare-earth silicon carbide ceramics, the silicon carbide bonding layer materials prepared using this method exhibit a significant improvement in thermal conductivity, increasing by 40-60%, which is crucial for applications requiring efficient heat dissipation. Simultaneously, the flexural strength of the silicon carbide bonding layer materials also increases by 1-15%, meaning the material demonstrates higher mechanical stability when resisting bending loads.
[0024] This invention not only solves the technical problem of uniform dispersion and structural maintenance of silicon carbide whiskers in silicon carbide bonding layer materials, but also significantly improves the thermal conductivity and mechanical properties of silicon carbide bonding layer materials, thus opening up broader application prospects for silicon carbide bonding layer materials. For example, it will demonstrate its unparalleled advantages in fields such as aerospace, energy devices, electronic packaging, and high-end equipment.
[0025] The present invention also provides a silicon carbide bonding layer material, wherein the composite ceramic is prepared by the above-described preparation method.
[0026] Preferably, the silicon carbide connecting layer material has a relative density greater than 97% and an open porosity of 0.1-1%. Compared with conventional composite ceramics, the silicon carbide connecting layer material prepared by this invention has a 40-60% increase in thermal conductivity and a 1-15% increase in flexural strength.
[0027] The present invention also provides a silicon carbide connecting member, wherein the silicon carbide connecting member is prepared by coating the above-mentioned silicon carbide connecting layer material into a slurry between two connecting parts, and then subjected to heat treatment.
[0028] Preferably, the connector is made of silicon carbide.
[0029] Further preferred, the silicon carbide material includes silicon carbide ceramic materials and / or silicon carbide ceramic matrix composites.
[0030] More preferably, the ceramic matrix composite material includes carbon fiber reinforced silicon carbide composite material and / or silicon carbide fiber reinforced silicon carbide composite material.
[0031] Preferably, the heat treatment includes one of electric field-assisted heating, microwave-assisted heating, pressureless heating, or hot-press heating.
[0032] Further optimization is to use a heating temperature of 900-2000℃.
[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0034] 1. This invention creatively uses rare earth hydrides, silicon carbide, and silicon carbide whiskers as raw materials. First, rare earth silicon carbide ceramic fine powder is prepared through solid-state synthesis and ball milling processes, ensuring that silicon carbide whiskers are uniformly dispersed in the ceramic powder. Through a series of rigorous process steps including drum mixing, drying, pre-pressing, and sintering, a silicon carbide bonding layer material is successfully prepared for the first time, in which the silicon carbide whiskers are uniformly distributed and structurally intact, confirming the effectiveness of the initial dispersion process.
[0035] 2. The preparation method of the present invention enables the silicon carbide bonding layer material to maintain structural integrity while improving thermal conductivity by 40-60% and bending strength by 1-15% compared to pure rare earth silicon carbide ceramics, greatly expanding its application prospects in various fields.
[0036] 3. This invention discloses a silicon carbide joining method, which uses silicon carbide whisker-reinforced rare earth silicon carbide ceramic as the joining layer material, and is expected to obtain joints with higher bending strength, corrosion resistance and high temperature resistance. Attached Figure Description
[0037] Figure 1 This is a scanning electron microscope image of the rare earth silicon carbide ceramic powder prepared in Example 1 after mixing with silicon carbide whiskers for 12 hours.
[0038] Figure 2 The SiC prepared in Example 1 of this invention w Scanning electron microscope image of the polished surface of the Y3Si2C2 bonding layer material.
[0039] Figure 3 SiC prepared in Example 1 w / RE3Si2C2 bonding layer material connection structure diagram, where RE is Y. Detailed Implementation
[0040] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0041] Example 1:
[0042] S1. YH2 powder with an average particle size of 75 μm and SiC powder with an average particle size of 0.5 μm were mixed at a molar ratio of 3.05:2. Then, anhydrous ethanol and zirconium oxide ball milling beads were added, followed by planetary ball milling, rotary evaporation, and sieving. The planetary ball mill speed was 300 r / min, and the ball milling time was 4 h. The powder was then calcined in a vacuum graphite pyrolysis furnace. The temperature in the vacuum graphite pyrolysis furnace was increased to 1300℃ at a rate of 10℃ / min and held for 5 h to obtain Y3Si2C2 ceramic powder.
[0043] S2 and Y3Si2C2 ceramic powders were added to anhydrous ethanol and zirconium oxide ball milling beads, and then subjected to planetary ball milling, rotary evaporation and sieving. The planetary ball mill speed was 300 r / min and the ball milling time was 8 h to obtain Y3Si2C2 ceramic powder with an average particle size of 1.59 μm.
[0044] S3. Prepare 5% of Y3Si2C2 ceramic with an average diameter of 0.5μm silicon carbide whiskers. Add anhydrous ethanol and zirconium oxide ball milling beads to the Y3Si2C2 ceramic. Mix the whiskers with the silicon carbide whiskers in a horizontal drum, rotary evaporate and sieve. Then, pack the mixture into a graphite mold and pre-press it into a block.
[0045] S4. SiC is prepared by sintering pre-compressed bulk materials using spark plasma sintering. w / Y3Si2C2 bonding layer material, wherein the discharge plasma sintering is carried out in an Ar atmosphere, with a heating and cooling rate of 50℃ / min, a temperature of 1400℃, a time of 15min, and a pressure of 30MPa.
[0046] The SiC prepared in Example 1 w The Y3Si2C2 bonding layer material was prepared into a slurry, and then... Figure 3 The coating was applied to the silicon carbide ceramic surface to be joined, and then the silicon carbide was joined at 1400°C using electric field-assisted heating to obtain the joined sample.
[0047] Figure 1 This is a scanning electron microscope (SEM) image of the rare-earth silicon-carbon ceramic powder prepared in Example 1 after being mixed with silicon carbide whiskers for 12 hours. After mixing, SiC... w It is uniformly dispersed in Y3Si2C2 ceramic powder and retains good integrity.
[0048] Figure 2 The SiC prepared in Example 1 of this invention w A scanning electron microscope (SEM) image of the polished surface of the Y3Si2C2 bonding layer material shows that the rare-earth silicon-carbon ceramic matrix has achieved complete densification. The silicon carbide whiskers retain good structural integrity after sintering, exhibiting excellent bonding with the rare-earth silicon-carbon ceramic, with virtually no whisker detachment.
[0049] Figure 3This is a schematic diagram of the silicon carbide whisker-reinforced rare earth silicon carbide composite ceramic connection structure prepared in Example 1, illustrating that the present invention, as a connecting layer material, is expected to obtain joints with higher bending strength, corrosion resistance, and high temperature resistance.
[0050] Example 2:
[0051] S1. YH2 powder with an average particle size of 75 μm and SiC powder with an average particle size of 0.5 μm were mixed at a molar ratio of 3.05:2. Then, anhydrous ethanol and zirconium oxide ball milling beads were added, followed by planetary ball milling, rotary evaporation, and sieving. The planetary ball mill speed was 300 r / min, and the ball milling time was 4 h. The powder was then calcined in a vacuum graphite pyrolysis furnace. The temperature in the vacuum graphite pyrolysis furnace was increased to 1300℃ at a rate of 10℃ / min and held for 5 h to obtain Y3Si2C2 ceramic powder.
[0052] S2 and Y3Si2C2 ceramic powders were added to anhydrous ethanol and zirconium oxide ball milling beads, and then subjected to planetary ball milling, rotary evaporation and sieving. The planetary ball mill speed was 300 r / min and the ball milling time was 8 h to obtain Y3Si2C2 ceramic powder with an average particle size of 1.59 μm.
[0053] S3. Prepare 10% of the mass of Y3Si2C2 ceramic silicon carbide whiskers with an average diameter of 0.5μm. Add them to Y3Si2C2 ceramic anhydrous ethanol and zirconium oxide ball milling beads, mix them in a horizontal drum, rotary evaporate and sieve, and then put them into a graphite mold to pre-press them into blocks.
[0054] S4. SiC is prepared by sintering pre-compressed bulk materials using spark plasma sintering. w / Y3Si2C2 bonding layer material, wherein the discharge plasma sintering is carried out in an Ar atmosphere, with a heating and cooling rate of 50℃ / min, a temperature of 1400℃, a time of 15min, and a pressure of 30MPa.
[0055] Example 3:
[0056] S1. DyH2 powder with an average particle size of 72 μm and SiC powder with an average particle size of 0.5 μm were mixed at a molar ratio of 3.05:2. Then, anhydrous ethanol and zirconium oxide ball milling beads were added, followed by planetary ball milling, rotary evaporation, and sieving. The planetary ball mill speed was 300 r / min, and the ball milling time was 4 h. Calcination was carried out using a vacuum graphite pyrolysis furnace. The vacuum graphite pyrolysis furnace was heated to 1200℃ at a rate of 10℃ / min and held for 5 h to obtain Dy3Si2C2 ceramic powder.
[0057] S2 and Dy3Si2C2 ceramic powders were added to anhydrous ethanol and zirconium oxide ball milling beads, and then subjected to planetary ball milling, rotary evaporation and sieving. The planetary ball mill speed was 300 r / min and the ball milling time was 8 h to obtain Dy3Si2C2 ceramic powder with an average particle size of 1.45 μm.
[0058] S3. Prepare 10% of Dy3Si2C2 ceramic with an average diameter of 0.5μm of silicon carbide whiskers. Add them to Y3Si2C2 ceramic with anhydrous ethanol and zirconium oxide ball milling beads. Mix them in a horizontal drum, rotary evaporate and sieve. Then, put them into a graphite mold and pre-press them into blocks.
[0059] S4. SiC is prepared by sintering pre-compressed bulk materials using spark plasma sintering. w / Dy3Si2C2 bonding layer material, wherein the discharge plasma sintering is carried out in an Ar atmosphere, with a heating and cooling rate of 50℃ / min, a temperature of 1200℃, a time of 15min, and a pressure of 30MPa.
[0060] Example 4:
[0061] S1. PrH2 powder with an average particle size of 80 μm and SiC powder with an average particle size of 0.5 μm were mixed at a molar ratio of 3.05:2. Then, anhydrous ethanol and zirconium oxide ball milling beads were added, followed by planetary ball milling, rotary evaporation, and sieving. The planetary ball mill speed was 300 r / min, and the ball milling time was 4 h. Calcination was carried out using a vacuum graphite pyrolysis furnace. The vacuum graphite pyrolysis furnace was heated to 1200℃ at a rate of 10℃ / min and held for 5 h to obtain Pr3Si2C2 ceramic powder.
[0062] S2 and Pr3Si2C2 ceramic powders were added to anhydrous ethanol and zirconium oxide ball milling beads, and then subjected to planetary ball milling, rotary evaporation and sieving. The planetary ball mill speed was 300 r / min and the ball milling time was 8 h to obtain Pr3Si2C2 ceramic powder with an average particle size of 1.73 μm.
[0063] S3. Prepare 10% of Pr3Si2C2 ceramic with an average diameter of 0.5μm of silicon carbide whiskers. Add them to Pr3Si2C2 ceramic with anhydrous ethanol and zirconium oxide ball milling beads. Mix them in a horizontal drum, rotary evaporate and sieve. Then, load them into a graphite mold and pre-press them into blocks.
[0064] S4. SiC is prepared by sintering pre-compressed bulk materials using spark plasma sintering. w / Pr3Si2C2 bonding layer material, wherein the discharge plasma sintering was carried out in an Ar atmosphere, with a heating and cooling rate of 50℃ / min, a temperature of 1100℃, a time of 15min, and a pressure of 30MPa.
[0065] Example 5:
[0066] The only difference from Example 1 is that the molar ratio of YH2 to silicon carbide is 5:1.
[0067] Example 6:
[0068] The only difference from Example 1 is that the molar ratio of YH2 to silicon carbide is 0.5:1.
[0069] Example 7:
[0070] The only difference from Example 1 is that the amount of silicon carbide whiskers added in step S3 is 0.5% of the mass of Y3Si2C2 ceramic.
[0071] Example 8:
[0072] The only difference from Example 1 is that the amount of silicon carbide whiskers added in step S3 is 20% of the mass of Y3Si2C2 ceramic.
[0073] Comparative Example 1:
[0074] The only difference from Example 1 is that step S2 was not performed.
[0075] Comparative Example 2:
[0076] The only difference from Example 1 is that steps S3 and S4 were not performed.
[0077] Comparative Example 3:
[0078] The only difference from Example 1 is that step S3 was not performed, and the Y3Si2C2 ceramic powder was directly sintered.
[0079] The materials prepared above were tested. The material prepared in Example 1 had a density of 4.464 and an open porosity of 0.19, showing a 41.7% increase in thermal conductivity and a 1.8% increase in flexural strength compared to the composite ceramic without added silicon carbide fibers. The material prepared in Example 2 had a density of 4.456 and an open porosity of 0.16, showing a 47.2% increase in thermal conductivity and a 9.1% increase in flexural strength compared to the composite ceramic without added silicon carbide fibers. The material prepared in Example 3 showed a 47.6% increase in thermal conductivity and a 9.5% increase in flexural strength compared to the composite ceramic without added silicon carbide fibers. The material prepared in Example 4 showed a 49.2% increase in thermal conductivity and a 10.3% increase in flexural strength compared to the composite ceramic without added silicon carbide fibers. The material prepared in Example 5, due to the addition of excessive rare earth hydrides, will generate a large amount of Y2O3 second phase during synthesis, resulting in reduced mechanical properties. The material prepared in Example 6 has reduced toughness due to residual unreacted silicon carbide. The material prepared in Example 7 has insufficient silicon carbide whiskers, resulting in insignificant reinforcing effect. The material prepared in Example 8 has excessive silicon carbide whiskers, leading to uneven whisker dispersion. Furthermore, the difference in thermal expansion coefficients between silicon carbide whiskers and rare earth silicon carbide ceramics results in excessive stress and reduced mechanical properties. The material prepared in Comparative Example 1 has reduced density and mechanical properties due to the large particle size of the sintering raw materials. The material prepared in Comparative Example 2 has a large-particle ceramic powder morphology because steps S3 and S4 were not performed. The material prepared in Comparative Example 3 has significantly reduced thermal conductivity and mechanical properties because no silicon carbide whiskers were added.
[0080] In summary, the preparation method of this invention enables the composite ceramic to maintain structural integrity while improving thermal conductivity by 40-60% and flexural strength by 1-15% compared to pure rare earth silicon carbide ceramics, greatly expanding its application prospects in various fields.
[0081] The embodiments described herein cover any points not exhaustively within the scope of the technical claims of this invention, as well as new technical solutions formed by equivalent substitutions of one or more technical features in the embodiments. These are all within the scope of the claims of this invention. Furthermore, in all listed or unlisted embodiments of this invention, each parameter in the same embodiment merely represents an instance (i.e., a feasible solution) of its technical solution, and there is no strict coordination or limitation relationship between the parameters. The parameters can be substituted for each other without violating axioms and the claims of this invention, unless otherwise stated.
[0082] The technical means disclosed in this invention are not limited to those described above, but also include technical solutions composed of any combination of the above technical features. The above descriptions are specific embodiments of this invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of this invention, and these improvements and modifications are also considered within the scope of protection of this invention.
[0083] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.
Claims
1. A method for preparing a silicon carbide bonding layer material, characterized in that, The method includes: S1. PrH2 powder with an average particle size of 80 μm and SiC powder with an average particle size of 0.5 μm were mixed at a molar ratio of 3.05:
2. Then, anhydrous ethanol and zirconium oxide ball milling beads were added, followed by planetary ball milling, rotary evaporation, and sieving. The planetary ball mill speed was 300 r / min, and the ball milling time was 4 h. Calcination was carried out using a vacuum graphite pyrolysis furnace. The vacuum graphite pyrolysis furnace was heated to 1200℃ at a rate of 10 ℃ / min and held for 5 h to obtain Pr3Si2C2 ceramic powder. S2 and Pr3Si2C2 ceramic powders were added to anhydrous ethanol and zirconium oxide ball milling beads, and then subjected to planetary ball milling, rotary evaporation and sieving. The planetary ball mill speed was 300 r / min and the ball milling time was 8 h to obtain Pr3Si2C2 ceramic powder with an average particle size of 1.73 μm. S3. Prepare 10% of Pr3Si2C2 ceramic with an average diameter of 0.5 μm of silicon carbide whiskers. Add them to Pr3Si2C2 ceramic with anhydrous ethanol and zirconium oxide ball milling beads. Mix them in a horizontal drum, rotary evaporate and sieve. Then, put them into a graphite mold and pre-press them into blocks. S4. SiC is prepared using spark plasma sintering pre-pressed bulk materials. w / Pr3Si2C2 bonding layer material, wherein the discharge plasma sintering was carried out in an Ar atmosphere, with a heating and cooling rate of 50 ℃ / min, a temperature of 1100 ℃, a time of 15 min, and a pressure of 30 MPa.
2. A silicon carbide bonding layer material, characterized in that, The connecting layer material is prepared by the preparation method described in claim 1.
3. A silicon carbide connecting component, characterized in that, The silicon carbide connecting member is prepared by coating the silicon carbide connecting layer material of claim 2 into a slurry between the two connecting members, and then subjecting it to heat treatment.
Citation Information
Patent Citations
Silicon carbide fiber bonding ceramic as well as preparation method and application thereof
CN117069505A
Boron carbide water cup liner production process
CN108298986A
Connecting material for connecting silicon carbide material, and application thereof
CN110357650A